IMPROVEMENT OF ACCOUNTING OF FINANCIAL RESULTS - Kholmurodov Otabek Normamatovich (Scholar Express Journals, 2024)
The article is devoted to the consideration of the issues of accounting of financial results of economic entities in reliance upon international financial reporting standards. Accounting of financial results are reflected in based on the data obtained from practice.
Keywords: Income; Expense; Profit; Accounting